MASALAH-MASALAH DALAM COVID-19 DAN HAK ASASI MANUSIA - Siti Rokayah; Gunawan Widjaja (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This research aims to analyze the problems in Covid-19 and Human Rights. This research is a normative juridical research that is descriptive in nature, and uses a prescriptive form with the aim of problem solution. The data used is secondary data which is analyzed qualitatively. The results of this study show that there are many problems that arise as a result of the Covid-19 pandemic and only the State can make policies to deal with the Covid-19 pandemic in accordance with human rights or not. The state should be wise in making policies whose contents are in accordance with human rights to deal with and deal with Covid-19. “Covid-19 does not discriminate, neither Should We”.